Laying the Groundwork for STEAM: Scaling and Supporting 3D Design and Printing in Higher Education - Harron, Jason R.; Emert, Randy; Thomas, Dominic M.; Campana, Jeff (Frontiers in Education, 2022)
This perspective article outlines the design and development of a 3D Printing Ecosystem (3DPE) that aims to lay the groundwork for STEAM education. The 3DPE is a coordinated system of hardware, software, and people that has been intentionally designed to scale computer-aided design (CAD) and 3D printing (3DP) at an institutional level. CAD and 3DP are two prime examples of technologies that support STEAM by blending engineering with the arts. These technologies, however, are typically only taught in select university courses that focus on engineering, product development, and industrial design. In recent years, the availability of affordable, reliable, and highly maintainable 3D printers has created an opportunity to infuse CAD and 3DP as a shared set of literacies that can cross disciplinary boundaries. The 3DPE consists of a decentralized series of 3DP labs, a centralized 3DP server, and faculty training. Using a train-the-trainer model, the 3DPE supports STEAM education by training faculty in CAD and 3DP while also providing ongoing curricular support to infuse these skills into their courses through project-based learning. This article provides preliminary examples of how the 3DPE is supporting STEAM education and offers advice for others seeking to replicate the model.